Mengangkat Potensi Lokal: Digitalisasi UMKM Kelurahan Gunung Lengkuas untuk Menembus Pasar Online - Shandika Yohana Siahaan; Nabilah Putri; Srimalo Muliani; Siti Faradilla Putri; Amanda Meyza; Rivaldi Fatwa Dwi Putra; Febri Zulhadi; Bima Ananta Birani (Pusat Riset dan Inovasi Nasional, 2025)
The MSME digitalization program in Gunung Lengkuas Village, implemented through the Community Service Program (KKN) of Raja Ali Haji Maritime University, primarily aims to increase the capacity of business actors in utilizing digital technology as a modern marketing tool. This program was designed in response to the challenge of low digital literacy experienced by most MSMEs, resulting in product marketing being limited to conventional methods and less able to compete in the wider market. The research used a qualitative approach with observation, interview, and documentation techniques throughout the 13-day implementation of the activity. Interventions were carried out in several stages, starting from socializing the importance of digitalization, technical training on the use of digital media, assistance in creating Google Business Profile and Instagram accounts, to compiling product catalogs in digital form and designing business logos. The results of the program implementation showed a significant increase in the understanding and skills of MSMEs in utilizing digital media, especially in expanding marketing reach, improving branding quality, and strengthening the competitiveness of local products. In addition, digitalization has been proven to have a positive impact on MSME independence and open up opportunities for greater contributions to the economic growth of the local community. Furthermore, this program also prepares business actors to face the challenges of competition in the global digital market, thus serving as a sustainable strategy to support the digital transformation of the MSME sector. Thus, this digitalization-based KKN activity not only provides practical benefits but also builds a strong foundation for technology-based local economic development